Reform in the making: CGIAR Research Program on Climate Change and Food Security (CCAFS) - Echeverrria, Ruben G. (International Center for Tropical Agriculture, 2011)
Presentation given by Ruben Echeverria, Director-General, International Centre for Tropical Agriculture (CIAT) at the celebration of the 40th Anniversary of CGIAR, at the FAO in Rome. 2 December 2011